Validation of a predictor of fatigue failure in the high-cycle range. (1st December 2020) - Szabó, Barna; Actis, Ricardo; Rusk, David
Abstract: A predictor of failure initiation in high-cycle fatigue was calibrated on the basis of uniaxial experimental data and its predictive performance tested against biaxial data. The procedures of solution verification, calibration, ranking, validation and uncertainty quantification were employed. A condition that defines the domain of the predictor is inferred from the results of validation experiments.